Improved cell signaling analysis by biofunctionalized nanospheres and imaging flow cytometry. Issue 11 (30th April 2021) - Koenig, Alice; Charmetant, Xavier; Barba, Thomas; Sicard, Antoine; Espi, Maxime; Dussurgey, Sébastien; Thaunat, Olivier
Abstract: The analysis of immune cell signaling is critical for the understanding of the biology and pathology of the immune system, and thus a mandatory step for the development of efficient biomarkers and targeted therapies. Phosflow, which has progressively replaced the traditional western blot approach, relies on flow cytometry to analyze various signaling pathways at a single‐cell level. This technique however suffers a lack of sensitivity largely due to the low signal/noise ratio that characterizes cell signaling analysis. In this study, we describe a new technique, which combines the use of biofunctionalized nanospheres (i.e., synthetic particulate antigens, SPAg) to stimulate the immune cells in suspension and imaging flow cytometry to identify homogenously‐stimulated cells and quantify the activity of the chosen signaling pathway in selected subcellular regions of interest. Using BCR signaling as model, we demonstrate that SIBERIAN (S PAg‐assI sted suB ‐cE llulaR sI gnaling AN alysis) allows assessing immune cell signaling with unprecedented sensitivity and specificity.